Preparation of layered double hydroxides (LDHS) for arsenate and chromate removal - Nhat Ha, Ho Nguyen; An, Tran Boi; Viet, Van; Mai Tho, Nguyen Thi; Thang, Tran Ngoc; Du, Cao Van; Kha, Nguyen Binh; Minh, Bui Quang; Phuong Dieu, Nguyen Thi; Kim Phuong, Nguyen Thi (Vietnam Journal of Chemistry, 2015)
Layer double hydroxides (LDHs) including MgFe-Cl (2:1), MgAl-Cl (2:1), ZnFe-Cl (2:1) and ZnAl-Cl (2:1) were synthesized by co-precipitation followed by calcination in air at 400 oC. The as-synthesized LDHs were characterized by powder X-Ray Diffraction, Scanning Electron Microscopy, Fourrier Transform Infrared spectroscopy and Brunauer Emmett Teller nitrogen adsorption method and tested for adsorption of arsenate (AsO43-) and chromate (CrO42-). The powder X-Ray Diffraction and Scanning Electron Microscopy revealed that the synthesized LDHs possess high crystallinity and hierarchical structure. At initial concentration ([AsO43-] or [CrO42-] = 100 mg/L), more than 99 % of AsO43- and CrO42- were removed by MgFe-Cl and MgAl-Cl. Approximately 71.62 % of AsO43-and 86.54 % of CrO42- were removed by ZnAl-Cl. While the removal of AsO43- and CrO42- by ZnFe-Cl were 78.33 % and 90.7 %,  respectively. Thus, present work has demonstrated that MgFe-Cl and MgAl-Cl is an interesting potential adsorbent application for AsO43- and CrO42- decontamination technology. Keywords. Layered double hydroxides, arsenate, chromate, removal.